Hubungan Pengetahuan Dan Sikap Remaja Tentang Pola Makan Seimbang Dengan Tindakan Pencegahan Diabetes Mellitus Tipe 2 - Nirmalasari, Novita; Supriatin, Rahayu Dwi (Indonesian Journal of Health Community; Vol 6 No 1 (2025): Volume 6 Nomor 1 Tahun 2025, 2025)
Diabetes mellitus is generally suffered by the elderly age group, but currently diabetes mellitus can also occur in adolescence. The main cause of type 2 diabetes mellitus in adolescents is an unbalanced lifestyle, including an unbalanced diet. The study aimed to find out the relationship between adolescents knowledge and attitudes about a balanced diet and preventive measures for type 2 diabetes mellitus at senior high school 10 Yogyakarta. The research design uses a quantitative method with proportionate stratified random sampling technique. The sample of this study was 93 respondents. The data were analyzed univariate and bivariate using Kendal's tau-b Test. The results were obtained between adolescents knowledge about diet with preventive measures for type 2 diabetes mellitus with a p-value of 0.010 (p?0.05) with a positive correlation of r=0.264 (0.2-0.399) and results between adolescents' attitudes about diet with preventive measures for type 2 diabetes mellitus with a p-value of 0.013 (p?0.05) with a positive correlation of r=0.300 (0.2-0.399). Interventions for preventing diabetes mellitus can be carried out, especially healthy living behavior. Future research can examine other factors, such as physical activity.